Ultrahigh piezoelectric performances of (K,Na)NbO3 based ceramics enabled by structural flexibility and grain orientation - Li-Feng Zhu; Dong Liu; Xiaoming Shi; Shiqing Deng; Jiecheng Liu; Li-Yu Wei; Zi-Qi Yang; Qi Wang; Bo-Ping Zhang; Houbing Huang; Shujun Zhang; Jing-Feng Li (Nature Communications)
Abstract (K,Na)NbO3-based ceramics are deemed among the most promising lead-free piezoelectric materials, though their overall piezoelectric performance still lags behind the mainstream lead-containing counterparts. Here, we achieve an ultrahigh piezoelectric charge coefficient d33 ∼ 807 pC·N−1, along with a high longitudinal electromechanical coupling factor (k33 ∼ 88%) and Curie temperature (Tc ∼ 245 °C) in the (K,Na)(Nb1-x Sb x )O3-Bi0.5Na0.5ZrO3-BiFeO3 (KNN-xSb) system through structural flexibility and grain orientation strategies. Phenomenological models, phase field simulations and high-angle annular dark-field scanning transmission electron microscopy reveal that the structural flexibility originates from the high Coulomb force between K+/Na+ ions and Sb ions in the KNN-xSb system, while the grain orientation promotes the displacement of B-site cations leveraging the engineered domain configuration. As a result of its excellent comprehensive piezoelectric properties, the textured KNN-5Sb/epoxy 1-3 piezoelectric composite is found to possess a broader bandwidth BW = 60% and higher amplitude output voltage than commercial PZT-5 and other KNN counterparts. These findings suggest that the textured KNN-5Sb ceramics could potentially replace current lead-based piezoceramics in transducer applications.